Assessing Antimicrobial Efficacy on Plastics and Other Non-Porous Surfaces: A Closer Look at Studies Using the ISO 22196:2011 Standard - Teresa Bento de Carvalho; Joana Bastos Barbosa; Paula Teixeira (Biology, 2024)
The survival and spread of foodborne and nosocomial-associated bacteria through high-touch surfaces or contamination-prone sites, in either healthcare, domestic or food industry settings, are not always prevented by the employment of sanitary hygiene protocols. Antimicrobial surface coatings have emerged as a solution to eradicate pathogenic bacteria and prevent future infections and even outbreaks. Standardised antimicrobial testing methods play a crucial role in validating the effectiveness of these materials and enabling their application in real-life settings, providing reliable results that allow for comparison between antimicrobial surfaces while assuring end-use product safety. This review provides an insight into the studies using ISO 22196, which is considered the gold standard for antimicrobial surface coatings and examines the current state of the art in antimicrobial testing methods. It primarily focuses on identifying pitfalls and how even small variations in methods can lead to different results, affecting the assessment of the antimicrobial activity of a particular product.